2017
DOI: 10.3389/fcimb.2017.00119
|View full text |Cite
|
Sign up to set email alerts
|

T3SS-Independent Uptake of the Short-Trip Toxin-Related Recombinant NleC Effector of Enteropathogenic Escherichia coli Leads to NF-κB p65 Cleavage

Abstract: Effector proteins secreted by the type 3 secretion system (T3SS) of pathogenic bacteria have been shown to precisely modulate important signaling cascades of the host for the benefit of the pathogens. Among others, the non-LEE encoded T3SS effector protein NleC of enteropathogenic Escherichia coli (EPEC) is a Zn-dependent metalloprotease and suppresses innate immune responses by directly targeting the NF-κB signaling pathway. Many pathogenic bacteria release potent bacterial toxins of the A-B type, which—in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 90 publications
0
25
0
Order By: Relevance
“…Tuning appropriate host response, especially PMN recruitment in response to pathogen aggression, is critical for host survival. PMN recruitment and activation during bacterial infection is a double-edged sword 30 . Neutropenic mice display exacerbated susceptibility of PA pneumonia 31 and neutrophil depletion (by i.v.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tuning appropriate host response, especially PMN recruitment in response to pathogen aggression, is critical for host survival. PMN recruitment and activation during bacterial infection is a double-edged sword 30 . Neutropenic mice display exacerbated susceptibility of PA pneumonia 31 and neutrophil depletion (by i.v.…”
Section: Discussionmentioning
confidence: 99%
“…administration of Ly6-G neutralisation antibody) which led to a fatal lung infection in our model within 12 hours (data not shown). Failure to properly control PMN accumulation following pulmonary infection will contribute to tissue damage and ARDS 26 , 30 , 32 . In the context of chronic obstructive pulmonary disease (COPD), Guillon et al .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of YopM in the cytoplasm (24% of total protein) 1 hr after incubation with HeLa cells, suggests that this protein can avoid lysosomal degradation by escaping to the cytoplasm before entering the nucleus (18.7% of total protein) (Scharnert et al, 2013) (Figure 1a). rNleC from EPEC also traffics to early and late endosomes, however, it is partially degraded in lysosomes (Stolle et al, 2017) (Figure 1b).…”
Section: Trafficking Of Nuclear-targeting Proteins Via the Endosomal-lysosomal Pathwaymentioning
confidence: 99%
“…Notably, by comparing the ratio of fluorescence from internalized rhodamine-labeled molecules to that of internalized naphthofluorescein-labeled molecules, the relative efficiencies of endosomal escape for different molecules-of-interest could be estimated. 35,163,[165][166][167] While these assays were designed to report exclusively on cytosolic localization, they required additional independent information, and they lacked absolute quantitation. Recently, a new fluorescence-based method was reported that provided absolute quantitation of fluorophore concentration in the cytosol (Figure 3c).…”
Section: Assays That Separate the Cytosol Using Ultracentrifugationmentioning
confidence: 99%